2015
DOI: 10.1088/0964-1726/24/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Polishing characteristics of optical glass using PMMA-coated carbonyl-iron-based magnetorheological fluid

Abstract: Soft magnetic carbonyl iron (CI) particles for magnetorheological (MR) polishing encounter corrosion problems as a result of their oxidation, leading to unpredictable polishing results. To overcome this issue, CI particles have been coated with either polymer or inorganic materials for improved MR polishing. In this study, CI particles were coated with poly(methyl methacrylate) to achieve improved MR polishing and anti-corrosion protection. In addition to an analysis of their rheological properties, a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…A reasonably smooth coating with some surface irregularities was produced, while the sedimentation stability of the MRF was enhanced. A similar work of grafting a PMMA coating onto CIP via dispersion polymerization has also been accomplished by Lee et al (2015) [ 57 ], but with further characterization on the performance of the coated CIP in MRF for the application of optical polishing. It was reported that the sedimentation ratio and anti-corrosion property of the coated material had increased, although the yield shear stress of the coated material in a magnetic field was lower than that of uncoated material.…”
Section: Coating Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…A reasonably smooth coating with some surface irregularities was produced, while the sedimentation stability of the MRF was enhanced. A similar work of grafting a PMMA coating onto CIP via dispersion polymerization has also been accomplished by Lee et al (2015) [ 57 ], but with further characterization on the performance of the coated CIP in MRF for the application of optical polishing. It was reported that the sedimentation ratio and anti-corrosion property of the coated material had increased, although the yield shear stress of the coated material in a magnetic field was lower than that of uncoated material.…”
Section: Coating Methodsmentioning
confidence: 96%
“…In other work conducted by Lee et al (2015) [ 57 ], the CIP was coated with PMMA to be applied in their own MR polishing fluid system. They discovered that by using PMMA-coated CIP in their MRF, the material removal depth of the BK7 glass workpiece was lower while exhibiting lower surface roughness than that of the uncoated one with an optimum rotating wheel speed of 1884 mm/s.…”
Section: Particle Coating In Mr Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerium oxide pellets [8] or soft-magnetic particles with magnetorheological fluid [9] could be used to make the polishing process more effective, yet these technologies can cause trouble in CNC polishing machining. The elastic properties of the pad material change in the polishing time, but they do not have the main influence on the surface quality [10].…”
Section: Introductionmentioning
confidence: 99%
“…Atlikti tyrimai su polimerais ar kitomis neorganinėmis medžiagomis padengtomis geležies dalelėmis, reguliuojant sukimosi greitį ir magnetinio lauko intensyvumą. Esant didesniam sukimosi greičiui pagreitėja medžiagos pašalinimas iš apdirbimo zonos, paviršiaus šiurkštumas mažesnis esant mažesniam magnetinio lauko intensyvumui (Lee et al 2015 santrauka. Straipsnyje aprašomas optinių detalių poliravimo procesas, naudojamosios technologijos ir medžiagos.…”
unclassified